Role of Neurokinin-1 and Dopamine Receptors on the Striatal Methamphetamine-Induced Proliferation of New Cells in Mice - Tulloch, Ingrid (2011)
A neurotoxic dose of methamphetamine (METH) induces the loss of some striatal neurons. Interestingly, the METH-induced apoptosis in the striatum is immediately followed by the generation of new cells (cytogenesis). In the present study, we investigated the role of the neurokinin-1, dopamine D1 and D2 receptors on the METH-induced cytogenesis. To that end, male mice were given a single injection (30 mg/kg, ip) or a binge of METH (10 mg/kg, 4X at two-hour intervals, ip). BrdU (100 mg/kg, ip) was given 36 hours after the last injection of METH. Newly generated cells were detected by immunohistochemistry and cell counts were performed using unbiased computerized stereology. Either single or binge exposure to METH resulted in the generation of new cells. The single optimized dose was used for subsequent mechanistic studies. Pretreatment with the dopamine D1 receptor antagonist SCH23390 (0.1 mg/kg, ip) 30 minutes prior to METH abrogated the METH-induced striatal cytogenesis. Pretreatment with the dopamine D2 receptor antagonist raclopride (1 mg/kg, ip) failed to affect this phenomenon. Finally, pretreatment with the neurokinin-1 receptor antagonist WIN 51,708 (5 mg/kg, ip) 30 minutes prior to METH abrogated the METH-induced cytogenesis. In conclusion, neurokinin-1 and dopamine D1 receptors are required for the METH-induced striatal cytogenesis while the D2 receptor is without effect.